Ectopic Papillary Thyroid Cancer with Distant Metastasis - Vázquez, Oscar R. (Case Rep Endocrinol, 2018)
Ectopic thyroid tissue is a rare clinical entity wherein malignant lesions may arise, the most common one being papillary carcinoma. We present a case of a 68-year-old female who presented with a growing mass in the right clavicle. An MR of the shoulder showed a soft tissue mass arising from the anterior margin of the right distal clavicle. A fine needle aspiration of the mass showed papillary thyroid carcinoma. PET/CT confirmed the clavicular and mediastinal mass. Excision of the clavicular mass and total thyroidectomy with modified right neck dissection were performed. Pathology revealed no evidence of malignancy in the thyroid; lymph nodes were positive for metastatic thyroid carcinoma. Postsurgery CT showed the superior mediastinal mass with surrounding adenopathy; radioiodine (RAI) treatment with dose of 142.1 mCi [5257.7 MBq] was recommended. Posttherapy whole-body scan (WBS) showed RAI avid tissue in the neck and superior mediastinum. Follow-up chest CT revealed pulmonary nodules that increased in number and size; a second RAI therapeutic dose was given. The posttherapy RAI WBS was negative. Repeat PET/CT showed multiple hypermetabolic lesions in the mediastinum, neck, lymph nodes, pulmonary nodes, and right shoulder. The FDG avid lesions with no RAI uptake suggested tumor dedifferentiation.